Transmission of electromagnetic beam through a uniaxial anisotropic slab. (February 2019) - Zhang, Huayong; Zhu, Dong; Wang, Mingjun; Li, Minquan; Liao, Tongqing
Highlight: Transmission of electromagnetic beam through a uniaxial anisotropic slab is obtained. The projection method is applied to the propagation problem. The normalized field intensity distributions are calculated. Abstract: We present a general theoretical scheme to investigate the propagation characteristics of a focused electromagnetic beam in a uniaxial anisotropic slab. The reflected, internal as well as transmitted waves are expanded in terms of cylindrical vector wave functions, and the unknown expansion coefficients are determined by virtue of the boundary conditions and the projection method. For incidence of a fundamental Gaussian beam, Hermite–Gaussian beam and doughnut mode beam, normalized field intensity distributions are evaluated and discussed briefly.